A novel splice variant of FcγRIIa: A risk factor for anaphylaxis in patients with hypogammaglobulinemia - van der Heijden, Joris; Geissler, Judy; van Mirre, Edwin; van Deuren, Marcel; van der Meer, Jos W.M.; Salama, Abdulgabar; van den Berg, Timo K.; Roos, Dirk; Kuijpers, Taco W. (Journal of allergy and clinical immunology, 2013)
Our index case was a patient with common variable immunodeficiency (CVID). She had anaphylactoid reactions on administration of intravenous immunoglobulin (IVIg) associated with the presence of IgG antibodies against IgA. We sought to determine the role of Fcγ receptor (FcγR) IIa in IVIg-induced anaphylactoid reactions. Neutrophils and PBMCs were isolated from healthy subjects and IVIg-treated patients. FcγRIIa mRNA and DNA were analyzed by using real-time PCR and sequencing. IgG-mediated elastase release and intracellular Ca2+ mobilization were determined in neutrophils and transfected cell lines, respectively. A novel splice variant of FcγRIIa containing an expressed cryptic exon 6* (FcγRIIaexon6∗) was identified in our index patient. This exon is normally spliced out of all FcγRII isoforms, except the inhibitory FcγRIIb1. Compared with healthy control subjects, the heterozygous FCGR2Ac.742+871A>G mutation was more frequent in patients with CVID (n = 53, P < .013). Expression in patients with CVID was associated with anaphylaxis on IVIg infusion (P = .002). On screening of additional IVIg-treated patient cohorts, we identified 6 FCGR2Ac.742+871A>G allele–positive patients with Kawasaki disease (n = 208) and 1 patient with idiopathic thrombocytopenia (n = 93). None had adverse reactions to IVIg. Moreover, FcγRIIaexon6∗ was also demonstrated in asymptomatic family members. Functional studies in primary cells and transfected murine cells demonstrated enhanced cellular activation by FcγRIIaexon6∗ compared with its native form, as shown by increased elastase release and intracellular calcium mobilization. A novel splice variant, FcγRIIaexon6∗, was characterized as a low-frequency allele, coding for a gain-of-function receptor for IgG. In the presence of immune complexes, FcγRIIaexon6∗ can contribute to anaphylaxis in patients with CVID.